Second-generation immigrants and factors that create challenges to enter Finnish labour market - Mangal, Abdul Haq (2018)
The aims of this study are to find out the most key factors that have negatively influenced second-generation immigrants with different foreign origins and ethnicities in their quest for job opportunities in the Finnish labour market. This stud‎y was done through qualitative research methods, which consisted of 15 second-generation immigrants, aged 18-35. These immigrants were divided into three main groups, which included European, Asian, and those of African backgrounds. This was to examine the role of ethnic aspects and to analyse the level of discrimination on different bases. The study was done through depth semi-structured face-to-face interviews. The questions which I asked the participants were in three parts: personal identification, role of parents’ background (social and educational) experiences of discrimination in the labour market in Finland, and the role of social networks with natives for entering to the Finnish labour market. Almost all participants having different immigrant’s origin reported that social network with the natives played a positive role in their entering of the job market. Visible minorities among the immigrants faced discrimination more than those who are from European backgrounds. This study focuses on the factors that affect the weak participation of second-generation immigrants in the Finnish labour market, or why second-generation immigrants have less possibility to get in the labour market. Perceived discrimination was on the bases of foreign name, appearance (skin color), and religion during the entry process and at the work place too. The results of this study show the importance and need for better integration. Accordingly, this thesis suggests the way forward for the Finnish government (policy makers) on how to improve, through policy implementation, to build strong social networks between immigrants and native Finns and suggestions to monitor the hidden discrimination against young immigrants.